Tactile Sensing Using Force Sensing Resistors and a Super-Resolution Algorithm - van den Heever, D.J.; Schreve, K.; Scheffer, C. (IEEE sensors journal, 2009)
This paper presents a tactile sensor consisting of an array of force sensing resistors (FSRs). The tactile sensing array can be seen as a coordinated system of touch sensors. The low spatial resolution measured with the FSRs compared to other force or pressure sensors required the use of a super-resolution algorithm. Super-resolution algorithms are often used in digital image processing to enhance the resolution of images. Multiple images taken from slightly different orientations are superimposed in such a way that a single higher-resolution image is obtained. Different touch sensors are briefly discussed and the use of FSRs is motivated. Image-registration techniques are discussed and the super-resolution algorithm developed for the application is presented. Some tests performed using the tactile sensor in a neck palpation device and the results of these tests are also presented.